Toward increasing leadership capacity in nurses: an exploration of the state and future perspectives of leadership education in pre-licensure baccalaureate nursing programs. - Miles, Jane (East Carolina University, 2015)
The purpose of this study was to explore and describe the state and future perspectives of leadership education in pre-licensure baccalaureate nursing programs. Study objectives were to describe nurse educator and practice leader perceptions regarding adequacy of leadership education and related research and scholarship in pre-licensure baccalaureate nursing programs, as well as components of existing nursing leadership education. Perceptions regarding the future of nursing leadership education, the leadership tasks used in an emerging nursing leadership development model, and the need for an initiative to support leadership education practices were also explored.   An exploratory descriptive, mixed-methods study was conducted surveying nurse educators and practice leaders with an interest in leadership education for nurses. Purposive sampling was used to survey the membership of the Council on Graduate Education for Administration in Nursing (CGEAN), and snowball sampling was used to include nurse educators who received the survey from CGEAN members. A researcher developed survey instrument supported collection of up to 38 items addressing the study objectives and participant characteristics.  Data analysis showed that the majority of participants believed leadership education and associated research and scholarship in pre-licensure baccalaureate nursing programs are inadequate to meet the needs of the nursing profession. Characteristics of existing leadership education included primarily stand-alone courses, a variety of pedagogies, and limited use of guiding frameworks and outcomes measurement instruments. Less than one-fourth of respondents were involved in related research. The tasks of leadership used in an emerging leadership development model for nurses were rated highly important to nursing. Regardless of their perception of leadership education adequacy, the majority of participants believed there is a need for a national initiative to address nursing leadership education.  The study contributes new nursing knowledge to inform processes for leadership education. A strong evidence base in leadership education is needed to support development of baccalaureate nursing undergraduates prepared to act upon their responsibility for leadership at all stages of their careers. This is a priority step in achieving the mission of nursing in positively influencing health care.
Keywords: Nursing; Leadership; Nursing education; Students; Baccalaureate; Education, Nursing, Baccalaureate--organization and administration; Professional Competence--standards; Education, Nursing, Graduate--standards; Education, Nursing, Graduate--trends